Efektivitas Penggunaan Teknologi dalam Meningkatkan Kinerja Pegawai Tata Usaha di MAN 2 Model Medan - Ningtias Aprili Maliyah; Muhammad Irwan Padli Nasution (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The main objective in this study was to find out how the quality of work of Administrative staff at Madrasah Aliyah Negeri 2 Model Medan. The type of research used in this research is descriptive qualitative. The number of administrative employees at MAN 2 Medan Model is 13 people. The results of this study are the work quality of Administrative staff of MAN 2 Model Medan. The results of the study showed that some employees only waited for orders from the Head of Administration to carry out the tasks that had to be done and even some employees did not do any work at all. Employees do not yet have a concrete and comprehensive plan for the work they will do.